Gas-liquid chromatography in the diagnosis of anaerobic infections: a three year experience. - Watt, B (J Clin Pathol, 1982)
Nearly two thousand clinical samples were examined by direct gas-liquid chromatography over a three year period. Absence of volatile fatty acids (VFAs) in the samples correlated well with negative culture results for anaerobic bacteria. In general the presence of acetic acid alone correlated well with the presence of aerobic organisms, whereas the presence of a mixture of VFAs correlated well with the presence of anaerobic organisms, either alone or in combination with aerobes. However a proportion of such VFA-positive samples gave no growth on culture. Swabs gave comparable results to samples of pus or exudates except that a higher proportion of the former were VFA-negative but culture positive.